Letter from Max Bredig to Thomas Blackadder, December 1938 - Bredig, Max Albert (1938)
Max Albert Bredig (1902-1977) asks Thomas Blackadder (1887-1953) for advice to help his father, Georg Bredig (1868-1944) immigrate to America. Max provides Blackadder with information about his own immigration.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Blackadder, Thomas, 1887-1953; Rohm and Haas Company; Emigration and immigration; Chemists